Spain : Recent Economic Developments and Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This Recent Economic Developments and Selected Issues paper highlights that after several years of relatively buoyant growth, Spain's economy went into recession in late 1992 and through 1993, but recovered rapidly in 1994 and early 1995. Toward the end of 1995, there was a renewed slowdown, though less marked than in other European countries, followed by a gradual acceleration during 1996. Over the three-year period 1994-96, GDP growth averaged 2.4 percent a year. The employment growth picked up relatively strongly in 1995 and 1996.